Bioefficacy of Plant Extracts to Control Cercospora Leaf Spot of Mungbean (Vigna radiata) - Uddin, MN; Bakr, MA; Islam, MR; Hossain, MI; Hossain, A (International Journal of Agricultural Research, Innovation and Technology, 2013)
The experiment was conducted at Bangladesh Agricultural Research Institute farm, Joydebpur, Gazipur during March to July 2007 to evaluate the bioefficacy of some plant extracts in controlling Cercospora leaf spot of mungbean. Six indigenous plant species i.e. Neem leaves extract (1:4 w/v), Garlic cloves extract (1:5 w/v), Biskatali leaves extract (1:4 w/v), Alamanda leaves extract (1:6 w/v), Arjun leaves extract (1:4 w/v) and Debdaru leaves extract (1:5 w/v) were used in this experiment. The experiment was laid out in RCBD with seven treatments and four replications. Data on disease incidence, severity, yield contributing characters and yield of mungbean were recorded. Naturally, infection of the disease was considered in this experiment. The lowest disease incidence (7.33%) at 60 DAS was found in T1. Lowest and similar disease severity (PDI= 4.55) was found in T2 and T3 at the same DAS. Neem extract treated plots gave better response in yield (1.26 t ha-1) and all the yield contributing parameters like inflorescences plant-1 (13.45), tallest plant (51.44 cm), the maximum number of pods plant-1 (26.81), length of pod (8.56 cm), number of seeds pod-1 (12.64) and 1000 seeds weight (27.33 g) followed by T2 and T3. The highest disease incidence (26.50%) and disease index (13.65%) were recorded in treatment T7 at 60 DAS. Yield and all yield contributing factors were lowest in same treatment. The results of the experiment suggested that the use of neem leaves extracts are effective for minimizing Cercospora leaf spot incidence, severity and increasing yield of mungbean. Int. J. Agril. Res. Innov. & Tech. 3 (1): 60-65, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16094